Engineering the MoS2/MXene Heterostructure for Precise and Noninvasive Diagnosis of Prostate Cancer with Clinical Specimens - Xie, Shaowei; Fei, Xiaochen; Wang, Jiayi; Zhu, Yi‐Cheng; Liu, Jiazhou; Du, Xinxing; Liu, Xuesong; Dong, Liang; Zhu, Yinjie; Pan, Jiahua; Dong, Baijun; Sha, Jianjun; et al. (Advanced science, 2023)
High‐throughput metabolic fingerprinting has been deemed one of the most promising strategies for addressing the high false positive rate of prostate cancer (PCa) diagnosis in the prostate‐specific antigen (PSA) gray zone. However, the current metabolic fingerprinting remains challenging in achieving high‐precision metabolite detection in complex biological samples (e.g., serum and urine). Herein, a novel self‐assembly MoS2/MXene heterostructure nanocomposite with a tailored doping ratio of 10% is presented as a matrix for laser desorption ionization mass spectrometry analysis in clinical biosamples. Notably, owing to the two‐dimensional architecture and doping effect, MoS2/MXene demonstrates favorable laser desorption ionization performance with low adsorption energy, which is evidenced by efficient urinary metabolic fingerprinting with an enhanced area under curve (AUC) diagnosis capability of 0.959 relative to that of serum metabolic fingerprinting (AUC = 0.902) for the diagnosis of PCa in the PSA gray zone. Thus, this MoS2/MXene heterostructure is anticipated to offer a novel strategy to precisely and noninvasively diagnose PCa in the PSA gray zone. A novel self‐assembling MoS2/MXene heterostructure is synthesized as a matrix for laser desorption ionization mass spectrometry analysis to accurately diagnose prostate cancer in the prostate‐specific antigen (PSA) gray zone, resulting in a diagnostic capability of 0.959 (area under curve, AUC). Thus, MoS2/MXene heterostructure is expected to provide a novel approach to prostate cancer management in the PSAgray zone.